Nuclear fusion energy-mankind's giant step forward - Lee, S.; Saw, S. H. (Springer US, 2011)
Estimates of energy supply versus consumption indicate the middle of this century as the critical point when world energy supply will no longer keep pace with the demand. The demand grows inexorably because of both the world population growth as well as the growth of average per capita energy consumption. Technological and economic progress are closely correlated with per capita energy consumption. Hence the inadequacy of energy supplies will limit the progress of human civilization, stifling its soaring spirit. Conservationism, making incremental improvements in this situation, is completely inadequate. What is needed is a giant step—the development of a new, limitless, clean source of energy—nuclear fusion energy. Nuclear fusion technology, when perfected to fusion-burn only deuterium, will have a fuel supply lasting millions of year, even with continuing energy consumption growth as in the past. Intensive efforts in five decades of Tokamak research has advanced the fusion product up by 107 times, to the point when breakeven is only a step away. The next step necessarily involves international collaboration on an unprecedented scale in ITER—the International Thermonuclear Experimental Reactor, on which work has started in Cadarache France. ITER and later Demo are envisioned to bring online the first commercial nuclear fusion energy reactor by 2050. Using this as the starting point and the history of the uptake of nuclear fission reactors as a guide, a scenario is described here which depicts a not unreasonable rapid take up of nuclear fusion energy starting after the middle of this century. Just into the next century fusion energy should be able to take up the slack and allow Mankind to continue its progress and growth. Because the development of fusion energy is such a complex technological task it is probable that there will be several decades when the constraints of energy shortage will be severely felt as shown by the flattening of the energy consumption from around 2040 to 2100. Such a period of stagnation seems unavoidable even with the envisaged development and rapid adoption of fusion energy. On the other hand without nuclear fusion energy the scenario depicts a severe downturn unavoidably in the fortunes of Mankind with world population shrinking below 5 billion and eventually even lower.